The Significance of the 2014 Corporate Governance Code of the Bank of Russia - A. V. Shashkova (Vestnik MGIMO-Universiteta)
The present article focuses on corporate governance in Russia, as well as on the approval in 2014 of the Code of Corporate Governance by the Bank of Russia and by the Russian Government. The article also provides the concept of the famous foreign term Compliance. Compliance is a system based on binding rules of conduct contained in the regulations which are mandatory for the company. In order to fulfill best practices and implement local acts on the most important issues for the company, many foreign companies as well as large Russian companies have formed special Compliance departments. Taking into account such international experience and international corporate governance principles the Bank of Russia has elaborated the Corporate Governance Code, approved by the Russian Government in February 2014. Corporate Governance Code regulates a number of the most important issues of corporate governance such as shareholders'rights and fair treatment of shareholders; Board of Directors; Corporate Secretary of the Company; system of remuneration of members of the Board of Directors, executive bodies and other key executives of the company; system of risk management and internal control; disclosure of information about the company, the information policy of the company; major corporate actions. The most important issue which is analyzed by the author is the problem of the composition of the Board of Directors: the presence of independent directors in the company. According to the author the new Corporate Governance Code reflects the latest trends as well as the current situation with corporate governance in Russia today.